Antibacterial activity of endophytic fungi in Pometia pinnata against Staphylococcus aureus and methicillin-resistant Staphylococcus aureus - Ratna Setyaningsih; Ari Susilowati; Dina Prasetyani (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Endophytic fungi associated with medicinal plants are able to produce bioactive compounds which potentially contain medicinal ingredients. Matoa (Pometia pinnata J. R. Forst & G. Forst) is one of Indonesian medicinal plants. This research aims to test antibacterial activities of ethyl acetate extract of matoa’s endophytic fungi to Staphylococcus aureus and Methicillin-resistant Staphylococcus aureus (MRSA) and also identify isolates having high antibacterial activity. Initial test on antibacterial activity was conducted by using paper disc diffusion, while advanced test was conducted by determining minimum inhibitory concentration (MIC). The fungi were identified in morphological and molecular manner with amplification and sequencing of ITS region. Bacterial cells exposed to the extract were observed by using scanning electron microscope (SEM). Isolate AM72 was found out to have the highest antibacterial activity compared to other 12 isolates tested, with inhibition zone diameter of 31.57 mm to S. aureus and 22.87 mm to MRSA. Isolate AM72 was identified as Lasiodiplodia theobromae. Isolate BMB identified as Aspergillus oryzae produced inhibition zone with 21.96 mm diameter to S. aureus and 21.50 mm diameter to MRSA. Advanced test to isolate AM72 gave the same MIC results to S. aureus and MRSA of 1.56%. Antibacterial compound produced by isolate AM72 were found out to be able to damage bacterial cell walls. Keywords: Antibacterial, Endohpytic Fungi, Matoa, S. aureus, MRSA